2022
DOI: 10.3390/magnetochemistry8020012
|View full text |Cite
|
Sign up to set email alerts
|

Soft Chemistry Synthesis and Characterization of CoFe1.8RE0.2O4 (RE3+ = Tb3+, Er3+) Ferrite

Abstract: Nanosized CoFe1.8RE0.2O4 (RE3+ = Tb3+, Er3+) ferrites were obtained through wet ferritization method. These ferrites were characterized by X-ray diffraction (XRD), scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM/HR-TEM), Fourier transform infrared spectroscopy (FTIR), Mössbauer spectroscopy and magnetic measurements. The XRD results revealed that the average crystallite size is 5.77 nm for CoFe1.8Tb0.2O4 and 6.42 nm for CoFe1.8Er0.2O4. Distribution of metal cations in the spinel st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…43 Gingasu reported the correlation of the hyperfine magnetic field at the Mossbauer nucleus with particle size and observed it to decrease with the decrease of particle volume. 44 Theoretical correlation between the cation distribution from Mossbauer spectroscopy was reported by Shan et al 24 However, unfortunately, such an important theoretical study is not available for Fe-rich CFO with RM-ion, specifically Dy 3+ , substitution. Further, to the best of our knowledge, either experimental or theoretical studies on the correlation of detailed cation distribution and magnetic properties for Fe-CFO are not available at this time.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…43 Gingasu reported the correlation of the hyperfine magnetic field at the Mossbauer nucleus with particle size and observed it to decrease with the decrease of particle volume. 44 Theoretical correlation between the cation distribution from Mossbauer spectroscopy was reported by Shan et al 24 However, unfortunately, such an important theoretical study is not available for Fe-rich CFO with RM-ion, specifically Dy 3+ , substitution. Further, to the best of our knowledge, either experimental or theoretical studies on the correlation of detailed cation distribution and magnetic properties for Fe-CFO are not available at this time.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Gasemi et al have concluded the substitution of Fe at the B-site based on the variation of the area of the B-site . Gingasu reported the correlation of the hyperfine magnetic field at the Mössbauer nucleus with particle size and observed it to decrease with the decrease of particle volume . Theoretical correlation between the cation distribution from Mössbauer spectroscopy was reported by Shan et al However, unfortunately, such an important theoretical study is not available for Fe-rich CFO with RM-ion, specifically Dy 3+ , substitution.…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of these methods is the use of precursors that are most often toxic, thereby limiting the scope of the application of the material. Since many nanoparticles are used in medicine and/or the cosmetic industry, new synthesis methods (the so-called green chemistry) have been developed that use safe and environmentally friendly nontoxic reagents [16,17]. A modern trend in the design of nanomaterials, especially magnetic nanomaterials, is the formation of hybrid structures of nanoparticle-polymer types that allow the functionalization and control of properties through the structure and composition of the polymer [18].…”
mentioning
confidence: 99%